“DO YOU NEED ENGLISH IN YOUR JOB?” SELF-EXPERIENCE FROM THREE INDONESIAN ALUMNI OF NON- ENGLISH DEPARTMENT - Shobaha, Shohiyah; Syarofi, Abdullah (JURNAL KONFIKS, 2025)
It is truthfully common that all colleges in Indonesia put English as the compulsory subject that must be learnt to improve the quality of alumni which enable them to compete in their future career. This study aims to find the perception of three Indonesian alumni of non-English department on English learning in university and their perspective on the use of English in their workplace based on their current self-experiences. This study employed a narrative inquiry design while the data were collected by using semi-structured interviews. Lastly, the data found were descriptively analyzed. The result of the present study confirms that three participants basically have awareness about the importance of English for their future career since they were in academic years, but their positive perspective turns to be slightly negative since they feel unsatisfied with the English teaching at college in the term of the materials taught and the method applied. However, their positive perspective about the importance of English in various sectors is strengthened by their real experience after coming to the career life. The result of this study is expected to give the new insight for students who are in the university-academic years about the urgency to learn English even though they are not majoring at English department and hopefully can be feedback for English lecturers who teach in non-English major to do improvement of teaching method and materials. The upcoming study expectantly can be conducted to investigate the comparation of the English needs between fresh graduate alumni and experienced alumni.